2017
DOI: 10.1186/s12931-017-0646-2
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory central airway collapse in stable COPD and during exacerbations

Abstract: BackgroundTracheal obstruction resulting from expiratory tracheal deformation has been associated with respiratory symptoms and severe airway exacerbations. In chronic obstructive pulmonary disease (COPD), acute exacerbations (AECOPD) create large intrathoracic pressure swings which may increase tracheal deformation. Excessive central airway collapse (ECAC) may be diagnosed when the tracheal area on expiration is less than 50% of that on inspiration. The prevalence of ECAC in AECOPD and its temporal course hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In general, most studies discussed imaging biomarkers either as prevalence values of radiological findings in a population of subjects with an exacerbation of COPD, or as quantitative measurements of an imaging feature. A total of 10 of the 51 papers [9][10][11][12][13][14][15][16][17][18] presented quantitative measurements of imaging features at exacerbation. One paper presented quantitative individual patient data, but no cohort averages, 19 and the remaining 40 papers presented prevalence values for established radiological or other features.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, most studies discussed imaging biomarkers either as prevalence values of radiological findings in a population of subjects with an exacerbation of COPD, or as quantitative measurements of an imaging feature. A total of 10 of the 51 papers [9][10][11][12][13][14][15][16][17][18] presented quantitative measurements of imaging features at exacerbation. One paper presented quantitative individual patient data, but no cohort averages, 19 and the remaining 40 papers presented prevalence values for established radiological or other features.…”
Section: Search Resultsmentioning
confidence: 99%
“…Most of these did not include details of any other imaging features and so are useful only in estimating the frequency of PE at exacerbation. Eleven serial imaging studies [10][11][12][14][15][16][17][18][19]30,31 performed imaging at multiple time-pointsusually at exacerbation and subsequent follow-up (assumed to represent recovery). The follow-up period for the second imaging time-point ranged from several days 17 to 16 months after the initial exacerbation imaging.…”
Section: Imaging Biomarkers Of Exacerbations Of Copd Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, central airway collapse using expiratory CT has been reported as an important clinical parameter in patients with COPD. Tracheal collapse during exhalation is prevalent in patients with COPD and related to worse St. George's Respiratory Questionnaire (SGRQ) scores and frequent exacerbation in these patients [ 8 , 9 ]. However, only a few reports have shown that expiratory bronchial area and expiratory bronchial collapse can be CT biomarkers that reflect lung function abnormalities in patients with COPD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8] The "E" in ECAC has been described as both expiratory and excessive without consistency. 2,3,9,10 Although this ambiguity may contribute to confusion, both terms describe the same pathologic entity. Excessive dynamic airway collapse refers to an excessive forward displacement of the posterior membranous portion of the tracheal wall due to weakness and atrophy of the longitudinal elastic fibers.…”
mentioning
confidence: 99%